Manisa Koldere Farm/Village’s Socio-Economic Situation According to Temettüât Registers (1844-1845) - Ferhat Berber (Gazi Akademik Bakış)
Koldere is a small municipality of Saruhanlı district of Manisa. It was a farm of Karaosmanoğlu notable family until the 19th century. Even after notables loss of power, the large part of the land remained as the property of Karaosmanoğlu Sadık Bey. When analysis the 1844-1845 temettüât register of the farm, it is seen the fact that the place was organized as a form of a village. However, the farm also plays an important role in agricultural production, as well as small ruminants. Furthermore, in the mid 19th century, almost all of the Koldere population consists of the Ottoman Greeks.